Writing the winning thesis or dissertation : a step-by-step guide - Joyner, Randy L.; Rouse, William A.; Glatthorn, Allan A., 1924-; Glatthorn, Allan A., 1924- (Thousand Oaks, Calif. : Corwin Press, 2013)
'This reader-friendly resource provides specific models and examples that break down the process into easily understood components with clear directions, from beginning to end. Major topics include: laying the groundwork for the thesis or dissertation; organizing and scheduling your work; collaborating with peers; using technology; solving problems throughout the dissertation process.'--
Laying the groundwork for the thesis and dissertation -- Dealing with institutional requirements -- Finding a research problem -- Conducting a focused review of the literature -- Making a preliminary choice of methodology -- Organizing and scheduling your work -- Developing the prospectus and organizing the committee -- Conducting a comprehensive critique of the literature -- Detailing the methodology -- Developing and defending the proposal -- Implementing the research design -- Mastering the academic style -- Organizing the dissertation -- Writing the introductory chapter -- Writing the review of the literature -- Explaining the methodology -- Presenting the results -- Summarizing and discussing the results -- Preparing and holding the dissertation defense -- Publishing from the thesis or dissertation.
Prev. ed. main entry under Glatthorn, Allan A.
Includes bibliographical references (p. 287-289) and index.
Keywords: Dissertations, Academic; Report writing; Research